The impact of physical activity on academic burnout in Chinese college students: a moderated chain mediation model - Xiang, Jiang; Jiang, Yun (Frontiers in Psychology, 2025)
BackgroundAcademic burnout has become increasingly prevalent among college students under multiple stressors. While earlier studies indicate that physical activity may be associated with lower levels of academic burnout, the specific processes involved remain insufficiently clarified.PurposeGuided by stress-coping theory and gender role theory, this study examined the potential chain mediation effects of social support and psychological capital on the relationship between physical activity and academic burnout among college students, as well as the moderating role of gender.MethodsUsing a random sampling method, a total of 858 valid questionnaires were collected, with male students accounting for 48.6% of the sample. Data were collected using standardized scales on college students’ perceptions of the study variables, with age and grade controlled for in the analyses, and the relationships among these variables were analyzed using bootstrapping methods.ResultsThe results indicated a significant negative correlation between physical activity and academic burnout. Both social support and psychological capital individually mediated this relationship, accounting for 14.5 and 10.1% of the total effect, respectively, while their combined chain mediation effect accounted for 23.2%. Furthermore, gender differences were observed: female students demonstrated a stronger effect of physical activity on enhancing social support, whereas male students exhibited a more pronounced effect of physical activity in directly mitigating academic burnout.ConclusionOverall, this study highlights plausible pathways through which physical activity may relate to academic burnout by fostering social support and psychological capital. These findings expand the current understanding of the association between physical activity and academic burnout, and offer valuable implications for educational practice.